Lip curve changes in males with premolar extraction or nonextraction treatment - Lin Pei-Ti; Woods Michael G. (Sciendo, 2004)
Aim: This retrospective study was designed to compare the responses of the upper and lower lip curves in young growing males, to orthodontic treatment involving either four premolar extractions or the holding of the E-spaces without premolar extractions.